Characterization of the [NiFe] Hydrogenase from the sulfate reducer Desulfovibrio vulgaris Hildenborough - Romão, Célia V. (1997)
The [NiFe] hydrogenase from Desulfovibrio vulgaris Hildenborough was isolated from the cytoplasmic membranes and characterized by EPR spectroscopy. It has a total molecular mass of 98.7 kDa (subunits of 66.4 and 32.3 kDa), and contains 1 nickel and 12 Fe atoms per heterodimer. The catalytic activities for hydrogen consumption and production were determined to be 174 and 89 umol H2 min-1 mg -1, respectively. As isolated, under aerobic conditions, this hydrogenase exhibits EPR signals characteristic of the nickel centers in [NiFe] hydrogenases (Ni-A signal at gx,y,z=2.32, 2.23 and ~2.0 and Ni-B signal at gx,y,z=2.33, 2.16 and ~2.0) as well as an intense quasi-isotropic signal centered at g=2.02 due to the oxidized [3Fe-4S] center. The redox proﬁle under hydrogen atmosphere is remarkably similar to that of other [NiFe] hydrogenases. The signals observed for the oxidized state disappear, ﬁrst being substituted by the Ni-C type signal (gx,y,z=2.19, 2.14, ~2.01), which upon long incubation under hydrogen yields the split Ni-C signal due to interaction with the reduced [4Fe-4S] centers.